Hemoglobin Level Decrease after Open Heart Surgery in a Tertiary Hospital in Indonesia - Anabella Nifulea; Reza Sudjud Widianto; Rama Nusjirwan (Althea Medical Journal, 2020)
Background: Open heart surgery is usually performed by connecting the heart to a cardiopulmonary bypass (CPB) machine. The use of the CPB machine may decrease the hemoglobin level and a very low hemoglobin levelcould cause seriouscomplications.This study aimed to explore the decrease in hemoglobin level after open heart surgery.Methods: A cross-sectional retrospective descriptive study was conducted on medical records of patients underwent coronary artery bypass graft (CABG) surgery and heart valve surgery in a tertiary hospital in Indonesia in  2018. The total sampling method was deployed to all medical records of patients underwent CABG surgery (n=25) and patients underwent heart valve surgery (n=3).Results: The decrease in hemoglobin level among young-adult female patients after heart valve surgery was 6.8 g/dl. The average decrease in mid-adult male and female patients after CABG surgery were 6 g/dl and 5.8 g/dl, respectively, and, after the heart valve surgery, the levels were 8.5 g/dl and 5.4 g/dl, respectively. The average decrease in Hb level among late-adult male and female patients after CABG surgery was 6.1 g/dl and 5.4 g/dl, respectively.Conclusion: Hemoglobin level decreases after an open heart surgery. Therefore, observation on the hemoglobin level to prevent complications and to facilitate early treatment is necessary.